Advanced phases and reduced amplitudes are suggested to characterize the daily rest-activity cycles in depressed adolescent boys. (9th August 2017) - Merikanto, Ilona; Partonen, Timo; Paunio, Tiina; Castaneda, Anu E.; Marttunen, Mauri; Urrila, Anna S.
Abstract: Self-reported eveningness has been previously associated with depressed mood among adults and adolescents. Here, we study how circadian indicators based on actigraphic data differ between depressed and healthy adolescent boys. Our sample consisted of 17 medication-free adolescent boys, aged 14.5 to 17.5 years, of which eight had depressive disorder and were currently depressed and nine were healthy comparison participants. Psychiatric assessment was conducted by diagnostic interviews and complemented with observer-rating and self-rating scales. Actigraphic data were collected with wrist actigraphs for a minimum period of 25 consecutive days (range of 25 to 44 days). The behavioral trait of morningness–eveningness was measured with the 19-item Horne-Östberg Morningness–Eveningness Questionnaire. Based on the self-report, the depressed boys were more prone to eveningness than healthy controls, but based on the actigraphic data, they had earlier phases especially on school days and lower activity levels especially on weekends. On weekends, the depressed boys showed a greater shift toward later-timed phases than healthy controls. Our results confirm a mismatch of the subjective morningness–eveningness preference (late-preference) and the objective rest-activity rhythm (early-prone) during school days in depressed adolescent boys.